Religião e mercado em Juazeiro do Norte : expressão do sagrado e do consumo religioso na terra do meu "Padim" - Andrelino, Paulo Cesar de Lima (2013)
The work aimed to make a critical analysis of the direct involvement of the person with the pilgrim trade a reality in the city of Juazeiro, where the visitor becomes significant amount of money. Above all, profit is sought, which allows to do a reading of the pilgrim not a creature, but as a benchmark for monetary value, enmeshed in consumerist market that is interwoven between goods and people who seek only the financial benefits. The shops, hostels and all other commercial establishments crave the long-awaited pilgrimage periods, certain guarantee economic stability until the next event that marks the timing of trips to the land of Father Cicero. Though faith and market mix, the pilgrim, devotee of fact, the sacred quest using a variety of routes and rituals to thank some grace achieved in previous times. The churches of the city favor the pilgrims with nonstop celebrations, although they also open their coffers for them to materialize the feelings of grateful pilgrims. The pomp often witnessed in Masses celebrated with the pilgrims allows them to perceive to be the temple-church where more easily God hears your prayers and entreaties. Therefore, the research is guided by reflecting this reality, analyzing prudently and judiciously logic, the attitudes of the pilgrims, the market and the Catholic Church opposite the relationship between the sacred - manifest in the practice of pilgrimages - and profane - personified in the consumption of objects, sacred or not, the market exposed the "holy city".